Effect of irrigation regimes on moisture extraction pattern, evapotranspiration and yield of fenugreek (Trigonella foenum-graecum L.) - R Chatterjee, S Datta (Journal of Spices and Aromatic Crops, 2006)
A field experiment was undertaken at Nadia (West Bengal) to study the effect of irrigationon moisture extraction pattern, evapotranspiration and yield of fenugreek (Trigonella foenum-graecum). The study revealed that irrigation influenced the moisture extraction pattern ofthe crop and higher amount of moisture was extracted from surface layer irrespective ofirrigation treatment and depletion of soil moisture increased with increasing level of irriga-tion. Seed yield and water use efficiency were influenced by different levels of irrigation. Thehighest water use efficiency was recorded in no irrigation and it was lowest in higher levelof irrigation at IW/CPE at 1.0. The highest seed yield, gross return, net return and benefit :cost ratio were recorded at IW/CPE ratio 1.0. Scheduling of irrigation at IW/CPE ratio 1.0was most beneficial followed by IW/CPE ratio 0.8 and irrigation at branching + flowering +seed development stages with respect to yield and return.